pharmaceutical-sciences 2018
DOI: 10.4172/pharmaceutical-sciences.1000333
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Localization and Production of Lovastatin from Monascus purpureus

Abstract: Seenivasan, et al.: Studies on Biosynthesis of LovastatinLovastatin is the first FDA-approved antihypercholesterolemic drug for the treatment of cardiovascular diseases. Monascus purpureus is one of the safest molds for the production of lovastatin that has been used in the preparation of Chinese medicine Red-yeast rice. This investigation dealt with the effect of both static and dynamic culture conditions on the morphological change and localization of lovastatin in Monascus purpureus. In dynamic culture cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
9
0
2
Order By: Relevance
“…1 ). The physicochemical and pharmaceutical properties of these two forms are different and interchangeable [ 6 , 41 ]. In the broth culture media, the filamentous fungi secrete lovastatin mostly in its hydroxy acid form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). The physicochemical and pharmaceutical properties of these two forms are different and interchangeable [ 6 , 41 ]. In the broth culture media, the filamentous fungi secrete lovastatin mostly in its hydroxy acid form.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the extracellular fraction of SM and SWW revealed a distinct pattern, such as stationary phase lines indicated the presence of non-lovastatin compounds. It has been reported three different maximum absorptions at 232, 238, and 247 nm of pure lovastatin, suggesting its better identification from other compounds, which is due to the presence of dienes [ 6 , 42 ]. The spectrophotometric analysis of lovastatin is easy, quick, eco-friendly, and less laborious than other analytical techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Inorganic salts are also essential in SmF by Monascus, such as metal ions such as Fe 2+ , Ca 2+ , Zn 2+ , Cu 2+ , Mg 2+ and Mn 2+ , which have been shown to promote cell growth and MK synthesis of Monascus in SmF [51]. Studies have shown that Mg 2+ and Mn 2+ have the most significant positive effect on MK production by Monascus SmF compared with other inorganic salts [52], and these two inorganic salts can even orchestrate their positive effects on MK synthesis when both are present [46]. In addition, Plackett-Burman design was used in other studies to analyze the effects of different inorganic salts on MK yield from Monascus.…”
Section: Inorganic Saltsmentioning
confidence: 99%
“…FDA (Food and Drug Administration) menerima Lovastatin sebagai obat antikolesterol pertama untuk terapi penyakit jantung dan kardiovaskuler (Seenivasan, Venkatesan, & Panda, 2018). Dari enam puluh orang pasien post CABG yang diberikan statin dan vitamin C hanya 10% yang mengalami fibrilasi atrial sedangkan pada kelompok kontrol yang tidak diberikan vitamin C mencapai 25% (Samadikhah et al, 2014).…”
Section: Pendahuluanunclassified
“…Keberadaan vitamin C menurunkan stabilitas ikatan antara lovastatin dengan enzim pencernaan, sehingga meningkatkan konsentrasi lovastatin bebas (Yang et al, 2020). Produksi lovastatin paling aman berasal dari kapang Monascus purpureus yang terdapat pada angkak (Seenivasan et al, 2018).…”
Section: Pendahuluanunclassified